The rate and cost of nurse turnover in Australia. Issue 4 (December 2015) - Roche, Michael A.; Duffield, Christine M.; Homer, Caroline; Buchan, James; Dimitrelis, Sofia
Summary: Nurse turnover is a critical issue facing workforce planners across the globe, particularly in light of protracted and continuing workforce shortages. An ageing population coupled with the rise in complex and chronic diseases, have contributed to increased demands placed on the health system and importantly, nurses who themselves are ageing. Costs associated with nurse turnover are attracting more attention; however, existing measurements of turnover show inconsistent findings, which can be attributed to differences in study design, metrics used to calculate turnover and variations in definitions for turnover. This paper will report the rates and costs of nurse turnover across three States in Australia.